The Genealogy of the Genealogical Method: Discoveries, Disseminations and the Historiography of British Anthropology1. Issue 3 (November 2016) - Gardner, Helen
Abstract : This article explores the origins of the genealogical method of kinship collection and the remembering and forgetting of Indigenous and settler contributors to early anthropology. While W. H. R. Rivers' development of the genealogical method from the expedition to the Torres Strait in 1898 has iconic status as a foundation moment in the history of anthropology, there is irrefutable evidence that a genealogical method for kinship collection was employed in the Australian colonies from the early 1870s, developed by Gunnai/Kŭrnai man Tulaba with magistrate A. W. Howitt. The article tracks the origins and dissemination of both genealogical methods and the crucial role of Indigenous agency in the development of field practices. It concludes with an analysis of the place of colonial ethnographers and Indigenous authorities in the historiography of British anthropology.